Water-based wear-resistant ceramic thermal insulation coating and preparation method thereof

By using water-based wear-resistant ceramic thermal insulation coatings, combined with a mixture of nano-antimony doped tin dioxide and nano-tungsten tin dioxide, polysiloxane resin and other additives, the problems of poor thermal insulation and poor weather resistance of existing building transparent maintenance structure thermal insulation coatings are solved, and high-efficiency thermal insulation, weather resistance and wear resistance are achieved.

CN119529668AActive Publication Date: 2025-02-28CHINA SOUTHWEST ARCHITECTURAL DESIGN & RES INST CORP LTD
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
CN202510108903.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-02-28
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The thermal insulation coatings of existing buildings' transparent maintenance structures have problems of poor thermal insulation and poor weather resistance, especially the high cost of nano-indium-doped tin dioxide and the unsatisfactory infrared band barrier effect.

Method used

A water-based wear-resistant ceramic heat-insulating coating is used, which consists of a mixture of nano-antimony doped tin dioxide and nano-tungsten tin dioxide, polysiloxane resin, 2-(2-hydroxyphenyl)-benzotriazole and alkali-hindered amine. Through the cooperation of modified nanoparticles and resin, a synergistic effect is formed to improve the thermal insulation, weather resistance and transparency of the coating.

Benefits of technology

It significantly improves the thermal insulation effect and weather resistance of the coating, provides good ultraviolet and infrared light barriers, enhances the hardness and wear resistance of the coating, and reduces the cost of raw materials, making it suitable for large-scale promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a water-based wear-resistant ceramic heat-insulating coating and a preparation method thereof, and relates to the field of coatings. The coating is prepared from the following raw material components in parts by weight: 20 to 50 parts of nano particle water-based dispersion liquid, 50 to 70 parts of polysiloxane resin, 20 to 40 parts of acrylic hydroxyl emulsion, 10 to 20 parts of organic solvent, 0.5 to 1 part of 2-(2-hydroxyphenyl)-benzotriazole and 0.5 to 1 part of alkaline hindered amine, the coating can effectively block transmission of ultraviolet light and infrared light, and the heat insulation effect is remarkable; the weather resistance, the scratch resistance, the water resistance and the hardness are excellent, and the wear-resistant and scratch-resistant protection effects are remarkable; meanwhile, the reflection and scattering effects on visible light are low, and the transmittance on the visible light is high; the coating is excellent in heat insulation effect, good in weather resistance, large in coating hardness, high in visible light transmission, low in raw material cost and suitable for large-scale application and popularization in transparent maintenance structures of buildings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, in particular to a water-based wear-resistant ceramic heat-insulating coating and a preparation method thereof. Background Art

[0002] The construction industry is transforming from "pursuing quantity" to "pursuing quality". Green buildings with "energy saving and efficiency improvement" are the preferred choice in the construction field. Among them, the insulation of transparent building envelopes has always been a difficulty in the industry. Early transparent building envelopes usually used curtains to block sunlight to play a role in insulation. Although curtains can block sunlight and play a partial insulation role, they will also store heat after long-term exposure to the sun in summer and become a heat source. In addition, blocking sunlight will affect activities in the building, increase lighting time, and waste electricity.

[0003] At present, the thermal insulation of transparent building envelope structures is mainly achieved by using polyurethane coatings prepared from nano-indium-doped tin dioxide (ITO) and nano-antimony-doped tin dioxide (ATO) particles. The high transparency of nano-indium-doped tin dioxide and nano-antimony-doped tin dioxide particles in the visible light band (380-780nm) and the blocking performance in the infrared band (780-2500nm) are mainly used to achieve the thermal insulation effect. It not only meets the high transmittance of most visible light bands, but also isolates most of the energy of the infrared spectrum band, thus achieving a certain thermal insulation effect.

[0004] In the market, nano antimony-doped tin dioxide technology is more widely used, while nano indium-doped tin dioxide technology is less used. This is because the price of nano indium-doped tin dioxide is too expensive, and its high cost seriously limits the wide application of the corresponding thermal insulation coating. In addition, in terms of infrared spectrum blocking, nano indium-doped tin dioxide only has the best blocking performance for the infrared band around 1400nm. However, the energy of the infrared band is mainly concentrated in 780-1100nm. Therefore, nano indium-doped tin dioxide has poor infrared blocking effect for the 780-1100nm band, which also causes its heat insulation effect to be unsatisfactory, and it has no blocking effect for the ultraviolet band. Although the price of nano antimony-doped tin dioxide is more appropriate, in terms of infrared spectrum blocking, nano antimony-doped tin dioxide also has the best blocking performance for the infrared band around 1100nm, and has poor blocking effect for the infrared band within 1000nm, so its heat insulation effect is also average, and it also has no blocking effect for the ultraviolet band.

[0005] At the same time, the existing thermal insulation coating is generally a polyurethane coating, which not only has a low hardness (generally <2H) and is easily scratched, thus affecting the transparency of the building's transparent maintenance structure; the weather resistance of the polyurethane coating is also poor, and long-term outdoor exposure is prone to problems such as powdering, cracking, and falling off, which also seriously affects the user experience and viewing experience of the building's transparent maintenance structure. Therefore, it is urgent to develop a coating material with good thermal insulation performance, which can effectively block most infrared bands, and has low cost and good weather resistance. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of poor thermal insulation effect and poor weather resistance of the existing thermal insulation coatings for transparent maintenance structures of buildings, and provide a water-based wear-resistant ceramic thermal insulation coating and a preparation method thereof. The coating formed by the coating not only has high transmittance to visible light, but also has good barrier effect for ultraviolet band and infrared band with a wavelength of 780-2500nm; at the same time, it also has the advantages of good weather resistance and high paint film hardness (hardness>4H), so that it has excellent thermal insulation effect and can provide good wear and scratch resistance for the transparent maintenance structure of the building, which is in line with the environmental protection concept of low-carbon energy-saving green buildings and is suitable for large-scale promotion and application.

[0007] In order to achieve the above-mentioned invention object, the present invention provides a water-based wear-resistant ceramic thermal insulation coating, comprising the following raw material components in parts by weight: 20-50 parts of an aqueous dispersion of nanoparticles, 50-70 parts of a polysiloxane resin, 20-40 parts of an acrylic hydroxyl emulsion, 10-20 parts of an organic solvent, 0.5-1 parts of 2-(2-hydroxyphenyl)-benzotriazole, and 0.5-1 parts of a basic hindered amine; The aqueous dispersion of nanoparticles contains 20-35% by mass of modified nanoparticles, wherein the modified nanoparticles are obtained by modifying the nanoparticles with a silane coupling agent; the nanoparticles are a mixture of nano-antimony-doped tin dioxide and nano-tungsten-doped tin dioxide in a mass ratio of 1-2:5-6.

[0008] The invention discloses a water-based wear-resistant ceramic heat-insulating coating. It not only forms a synergistic effect by using antimony- and tungsten-doped tin dioxide nanoparticles in combination with 2-(2-hydroxyphenyl)-benzotriazole and alkaline hindered amine, so that the coating can effectively block the transmission of ultraviolet light and infrared light, and significantly improves the heat-insulating effect of the coating; but also uses a polysiloxane resin with a three-dimensional network structure as a coating film-forming substance, so that the coating is endowed with excellent weather resistance, scratch resistance, water resistance and hardness, and significantly improves the wear-resistant and scratch-resistant protective effect of the coating; at the same time, targeted modification treatment is performed on the nanoparticles according to the type of the matrix resin, so that the nanoparticles can be better dispersed in the coating system, and the interface compatibility between the nanoparticles and the resin matrix is ​​significantly increased, so that the reflection and scattering effects of the coating on visible light are significantly reduced, and the transmittance of visible light is significantly increased (not less than 82%); the coating has excellent heat-insulating effect, good weather resistance, high coating hardness, high visible light transmittance, low raw material cost, and is suitable for large-scale promotion and use in transparent maintenance structures of buildings.

[0009] Among them, preferably, the polysiloxane resin is an organic-inorganic hybrid water-based silicone resin formed by hydrolysis and condensation of silane monomer and acidic silica sol; the polysiloxane resin has a three-dimensional network structure, which can make the coating formed after curing have excellent weather resistance, scratch resistance, water resistance and hardness, and can provide good wear and scratch resistance protection for the transparent maintenance structure of the building; more preferably, the specific method for synthesizing the polysiloxane resin includes: adding a catalyst to the silane monomer, then adding acidic silica sol, and mixing and reacting at a temperature of 25±2°C for 1.5-2.5h to obtain it.

[0010] Preferably, the silane monomer is at least one of methyl orthosilicate, ethyl orthosilicate, methyltrimethoxysilane, phenyltrimethoxysilane, dimethyldimethoxysilane and 3-glycidyloxypropyltrimethoxysilane; the preferred type of silane monomer has better properties of the formed polysiloxane resin and the formed coating has higher transmittance to visible light.

[0011] Preferably, the acidic silica sol is a special colloidal solution mainly composed of silicon dioxide (SiO 2 ) The particles are evenly dispersed in water with a pH value of 2-4.

[0012] Preferably, in the synthesis method of the polysiloxane resin, the mass ratio of the silane monomer to the acidic silica sol is 5-10:2-5; at the preferred mass ratio, the synthesized polysiloxane resin has better properties and the formed coating has higher transmittance to visible light.

[0013] Preferably, the catalyst is acetic acid, formic acid or hydrochloric acid.

[0014] Preferably, the added amount of the catalyst is 0.2-1% of the mass of the silane monomer.

[0015] Wherein, the acrylic hydroxy emulsion is an aqueous emulsion; preferably, the acrylic hydroxy emulsion is a polymerized hydroxy acrylic emulsion with a solid content of 30%.

[0016] Among them, preferably, the organic solvent is an ethanol solution of propylene glycol methyl ether or an ethanol solution of ethylene glycol butyl ether; the preferred organic solvent can make the raw materials in the coating more evenly dispersed, and the obtained coating has a higher transmittance to visible light.

[0017] Preferably, in the organic solvent, the mass percentage of ethanol is 40-60%.

[0018] Wherein, the basic hindered amine is a nitroxide free radical hindered amine (NOR type); more preferably, the basic hindered amine is one or more of 2,2,6,6-tetramethylpiperidine and its substituted derivatives.

[0019] Among them, the nanoparticles are modified by a coupling agent to increase the steric hindrance between the nanoparticles, improve the aqueous dispersibility of the nanoparticles, prevent agglomeration, and disperse the nanoparticles more evenly in the coating, and significantly increase the transmittance of the coating to visible light; preferably, during the modification treatment, the added amount of the silane coupling agent is 0.3-0.8% of the nanoparticles.

[0020] Preferably, the silane coupling agent is a mixture of γ-methacryloxypropyltrimethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane in a mass ratio of 4-10:1-2.

[0021] Preferably, the modification method of the nanoparticles comprises: mixing the nanoparticles and a silane coupling agent, and then performing oscillation grinding with zirconium oxide beads for 2-4 hours to obtain the nanoparticles.

[0022] Among them, the smaller the particle size of the nanoparticles, the better the ultraviolet and infrared light blocking effect, the better the visible light transmittance, but the dispersibility is reduced. Therefore, the appropriate nanoparticle size range can make the coating have better ultraviolet and infrared light blocking effect, higher visible light transmittance, and better dispersibility, which is conducive to improving the performance of the coating. Preferably, the particle size of the nanoparticles is 2-20nm; more preferably, the particle size of the nanoparticles is 5-10nm.

[0023] Preferably, the method for preparing the aqueous dispersion of nanoparticles comprises: adding the modified nanoparticles into deionized water, then adding an aqueous dispersant and an aqueous wetting agent, and dispersing the mixture by ultrasonication for 2-3 hours to obtain the aqueous dispersion.

[0024] Preferably, the aqueous dispersant is a high molecular weight polyacrylate dispersant, such as AFCONA-4595, AFCONA-4599, TEGO-755W, TEGO-760W, BYK-190, etc.; and its usage is 1-3% of the mass of the nanoparticles.

[0025] Preferably, the aqueous wetting agent is a silicone wetting agent, such as AFCONA-3580, BYK-331, BYK-346, etc.; the dosage is 0.5-1.5% of the mass of the nanoparticles.

[0026] Furthermore, in order to achieve the above-mentioned purpose of the invention, the present invention also provides a method for preparing a water-based wear-resistant ceramic thermal insulation coating, comprising: mixing the above-mentioned raw materials evenly according to the formula to obtain the water-based wear-resistant ceramic thermal insulation coating.

[0027] Compared with the prior art, the present invention has the following beneficial effects: 1. The water-based wear-resistant ceramic thermal insulation coating of the present invention forms a synergistic effect by using tin dioxide nanoparticles doped with antimony and tungsten in combination with 2-(2-hydroxyphenyl)-benzotriazole and alkaline hindered amine, so that the coating can effectively block the transmission of ultraviolet light (the total ultraviolet light blocking rate in natural light is not less than 98%) and infrared light (the total infrared light blocking rate in natural light is not less than 90%), thereby significantly improving the thermal insulation effect of the coating.

[0028] 2. The water-based wear-resistant ceramic thermal insulation coating of the present invention uses a polysiloxane resin with a three-dimensional network structure as the coating film-forming substance, thereby giving the coating excellent weather resistance, scratch resistance, water resistance and hardness, and significantly improving the wear-resistant and anti-scratch protection effect of the coating.

[0029] 3. The water-based wear-resistant ceramic thermal insulation coating of the present invention has carried out targeted modification treatment on the nanoparticles according to the type of the matrix resin, so that the nanoparticles can be better dispersed in the coating system and the interfacial compatibility between the nanoparticles and the resin matrix is ​​significantly increased, thereby significantly reducing the reflection and scattering effects of the coating on visible light and significantly improving the transmittance of visible light (not less than 82%).

[0030] 4. The water-based wear-resistant ceramic thermal insulation coating of the present invention has excellent thermal insulation effect, good weather resistance, high coating hardness, high visible light transmittance, low raw material cost, and is suitable for large-scale promotion and use in transparent building maintenance structures. DETAILED DESCRIPTION

[0031] In order to more clearly describe the invention purpose, technical scheme and technical effect advantages in the specific implementation case of the present invention, the scheme in the specific embodiment of the present invention will be described in detail below. The specific technical scheme involved in the following specific embodiments is only for a clear and complete description of the innovative technical scheme of the present invention. It is only a part of the specific implementation scheme that can be adopted by the present invention, not all embodiments, and should not be understood as a limitation on the innovative scheme of the present invention. Any scheme adopting the same inventive concept of the present invention should be included in the protection scope of the present invention.

[0032] For those skilled in the art, when understanding the solutions described in the specific embodiments of the present invention, they can refer to the conventional technical manuals in the field. At the same time, for the places where the above-mentioned terms appear, they can make appropriate understandings or adjustments for reference, and deduce the implementation of the same or similar technical solutions without paying any creative work.

[0033] Example 1 A water-based wear-resistant ceramic heat-insulating coating is prepared by mixing the following raw material components in parts by weight: 35 parts of nanoparticle aqueous dispersion, 60 parts of polysiloxane resin, 30 parts of acrylic hydroxyl emulsion, 15 parts of organic solvent, 0.8 parts of 2-(2-hydroxyphenyl)-benzotriazole, and 0.8 parts of alkaline hindered amine (2,2,6,6-tetramethylpiperidine).

[0034] The preparation method of the aqueous dispersion of nanoparticles includes: adding 30 parts of modified nanoparticles to 69.8 parts of deionized water, and then adding 0.6 parts of aqueous dispersant (AFCONA-4595) and 0.3 parts of aqueous wetting agent (AFCONA-3580), and using ultrasonic dispersion for 2.5 hours to obtain; The modified nanoparticles are obtained by modifying the nanoparticles with a silane coupling agent (a mixture of γ-methacryloxypropyltrimethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane in a mass ratio of 6:1), and the specific method includes: mixing 700 parts of the nanoparticles with 4.5 parts of the silane coupling agent, and then grinding with zirconium oxide beads for 3 hours; The nanoparticles are a mixture of nano antimony-doped tin dioxide (particle size 8 nm) and nano tungsten-doped tin dioxide (particle size 6 nm) in a mass ratio of 3:11; The specific method for synthesizing the polysiloxane resin includes: adding 0.55 parts of a catalyst (acetic acid) to 85 parts of a silane monomer (methyl orthosilicate), then adding 35 parts of an acidic silica sol (pH value is 3), and mixing and reacting at a temperature of 25°C for 2 hours to obtain; The organic solvent is an ethanol solution of propylene glycol methyl ether, and the mass fraction of ethanol is 50%; Acrylic hydroxyl emulsion is a polymerized hydroxyl acrylic emulsion with a solid content of 30%.

[0035] Example 2 A water-based wear-resistant ceramic heat-insulating coating is prepared by mixing the following raw material components in parts by weight: 20 parts of nanoparticle aqueous dispersion, 50 parts of polysiloxane resin, 20 parts of acrylic hydroxyl emulsion, 10 parts of organic solvent, 1 part of 2-(2-hydroxyphenyl)-benzotriazole, and 1 part of alkaline hindered amine (2,2,6,6-tetramethylpiperidine).

[0036] The preparation method of the aqueous dispersion of nanoparticles includes: adding 35 parts of modified nanoparticles to 64.3 parts of deionized water, and then adding 1.05 parts of an aqueous dispersant (BYK-190) and 0.525 parts of an aqueous wetting agent (BYK-331), and dispersing by ultrasonication for 3 hours to obtain; The modified nanoparticles are obtained by modifying the nanoparticles with a silane coupling agent (a mixture of γ-methacryloxypropyltrimethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane in a mass ratio of 4:1), and the specific method includes: mixing 800 parts of the nanoparticles with 6 parts of the silane coupling agent, and then grinding with zirconium oxide beads for 4 hours; The nanoparticles are a mixture of nano antimony-doped tin dioxide (particle size 10 nm) and nano tungsten-doped tin dioxide (particle size 10 nm) in a mass ratio of 1:5; The specific method for synthesizing the polysiloxane resin includes: adding 1 part of a catalyst (acetic acid) to 100 parts of a silane monomer (methyltrimethoxysilane), then adding 50 parts of an acidic silica sol (pH value is 2), and mixing and reacting at a temperature of 27°C for 1.5 hours to obtain; The organic solvent is an ethanol solution of ethylene glycol butyl ether, and the mass fraction of ethanol is 60%; Acrylic hydroxyl emulsion is a polymerized hydroxyl acrylic emulsion with a solid content of 30%.

[0037] Example 3 A water-based wear-resistant ceramic thermal insulation coating is prepared by mixing the following raw material components in parts by weight: 50 parts of a nanoparticle aqueous dispersion, 70 parts of a polysiloxane resin, 40 parts of an acrylic hydroxyl emulsion, 20 parts of an organic solvent, 0.5 parts of 2-(2-hydroxyphenyl)-benzotriazole, and 0.5 parts of a basic hindered amine (4-acetamido-2,2,6,6-tetramethylpiperidine).

[0038] The preparation method of the aqueous dispersion of nanoparticles includes: adding 20 parts of modified nanoparticles to 79.5 parts of deionized water, and then adding 0.2 parts of aqueous dispersant (TEGO-755W) and 0.1 parts of aqueous wetting agent (BYK-346), and using ultrasonic dispersion for 2.0 hours to obtain; The modified nanoparticles are obtained by modifying the nanoparticles with a silane coupling agent (a mixture of γ-methacryloxypropyltrimethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane in a mass ratio of 10:1), and the specific method includes: mixing 600 parts of the nanoparticles with 2.5 parts of the silane coupling agent, and then grinding with zirconium oxide beads for 2 hours; The nanoparticles are a mixture of nano-antimony-doped tin dioxide (particle size 5 nm) and nano-tungsten-doped tin dioxide (particle size 6 nm) in a mass ratio of 1:3; The specific method for synthesizing the polysiloxane resin includes: adding 0.1 part of a catalyst (acetic acid) to 50 parts of a silane monomer (1:1 methyltrimethoxysilane and dimethyldimethoxysilane), then adding 20 parts of an acidic silica sol (pH value is 4), and mixing and reacting at a temperature of 23°C for 1.5 hours to obtain; The organic solvent is an ethanol solution of propylene glycol methyl ether, and the mass fraction of ethanol is 40%; Acrylic hydroxyl emulsion is a polymerized hydroxyl acrylic emulsion with a solid content of 30%.

[0039] Example 4 A water-based wear-resistant ceramic heat-insulating coating is prepared by mixing the following raw material components in parts by weight: 35 parts of nanoparticle aqueous dispersion, 60 parts of polysiloxane resin, 30 parts of acrylic hydroxyl emulsion, 15 parts of organic solvent, 0.8 parts of 2-(2-hydroxyphenyl)-benzotriazole, and 0.8 parts of alkaline hindered amine (2,2,6,6-tetramethylpiperidine).

[0040] The preparation method of the aqueous dispersion of nanoparticles includes: adding 30 parts of modified nanoparticles to 69.8 parts of deionized water, and then adding 0.6 parts of aqueous dispersant (AFCONA-4599) and 0.3 parts of aqueous wetting agent (AFCONA-3580), and using ultrasonic dispersion for 2.5 hours to obtain; The modified nanoparticles are obtained by modifying the nanoparticles with a silane coupling agent (a mixture of γ-methacryloxypropyltrimethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane in a mass ratio of 6:1), and the specific method includes: mixing 700 parts of the nanoparticles with 2.0 parts of the silane coupling agent, and then grinding with zirconium oxide beads for 2 hours; The nanoparticles are a mixture of nano antimony-doped tin dioxide (particle size 20 nm) and nano tungsten-doped tin dioxide (particle size 20 nm) in a mass ratio of 3:11; The specific method for synthesizing the polysiloxane resin includes: adding 0.55 parts of a catalyst (acetic acid) to 85 parts of a silane monomer (methyl orthosilicate), then adding 35 parts of an acidic silica sol (pH value is 3), and mixing and reacting at a temperature of 25°C for 2 hours to obtain; The organic solvent is an ethanol solution of propylene glycol methyl ether, and the mass fraction of ethanol is 50%; Acrylic hydroxyl emulsion is a polymerized hydroxyl acrylic emulsion with a solid content of 30%.

[0041] Example 5 A water-based wear-resistant ceramic heat-insulating coating is prepared by mixing the following raw material components in parts by weight: 35 parts of nanoparticle aqueous dispersion, 60 parts of polysiloxane resin, 30 parts of acrylic hydroxyl emulsion, 15 parts of organic solvent, 0.8 parts of 2-(2-hydroxyphenyl)-benzotriazole, and 0.8 parts of alkaline hindered amine (2,2,6,6-tetramethylpiperidine).

[0042] The preparation method of the aqueous dispersion of nanoparticles includes: adding 30 parts of modified nanoparticles to 69.8 parts of deionized water, and then adding 0.6 parts of aqueous dispersant (TEGO-760W) and 0.3 parts of aqueous wetting agent (BYK-331), and using ultrasonic dispersion for 2.5 hours to obtain; The modified nanoparticles are obtained by modifying the nanoparticles with a silane coupling agent (a mixture of γ-methacryloxypropyltrimethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane in a mass ratio of 1.5:1), and the specific method includes: mixing 700 parts of the nanoparticles with 4.5 parts of the silane coupling agent, and then grinding with zirconium oxide beads for 3 hours; The nanoparticles are a mixture of nano antimony-doped tin dioxide (particle size 8 nm) and nano tungsten-doped tin dioxide (particle size 6 nm) in a mass ratio of 3:11; The specific method for synthesizing the polysiloxane resin includes: adding 0.55 parts of a catalyst (acetic acid) to 85 parts of a silane monomer (methyl orthosilicate), then adding 55 parts of an acidic silica sol (pH value is 3), and mixing and reacting at a temperature of 25° C. for 4 hours to obtain; The organic solvent is an ethanol solution of propylene glycol methyl ether, and the mass fraction of ethanol is 30%; Acrylic hydroxyl emulsion is a polymerized hydroxyl acrylic emulsion with a solid content of 30%.

[0043] Example 6 A water-based wear-resistant ceramic heat-insulating coating is prepared by mixing the following raw material components in parts by weight: 35 parts of nanoparticle aqueous dispersion, 60 parts of polysiloxane resin, 30 parts of acrylic hydroxyl emulsion, 15 parts of organic solvent, 0.8 parts of 2-(2-hydroxyphenyl)-benzotriazole, and 0.8 parts of alkaline hindered amine (2,2,6,6-tetramethylpiperidine).

[0044] The preparation method of the aqueous dispersion of nanoparticles includes: adding 30 parts of modified nanoparticles to 69.8 parts of deionized water, and then adding 0.6 parts of an aqueous dispersant (BYK-190), and using ultrasonic dispersion for 5 hours to obtain; The modified nanoparticles are obtained by modifying the nanoparticles with a silane coupling agent (a mixture of γ-methacryloxypropyltrimethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane in a mass ratio of 6:1), and the specific method includes: mixing 700 parts of the nanoparticles with 4.5 parts of the silane coupling agent, and then grinding with zirconium oxide beads for 3 hours; The nanoparticles are a mixture of nano antimony-doped tin dioxide (particle size 2 nm) and nano tungsten-doped tin dioxide (particle size 2 nm) in a mass ratio of 3:11; The specific method for synthesizing the polysiloxane resin includes: adding 0.55 parts of a catalyst (acetic acid) to 85 parts of a silane monomer (methyl orthosilicate), then adding 35 parts of an acidic silica sol (pH value is 3), and mixing and reacting at a temperature of 25°C for 2 hours to obtain; The organic solvent is a methanol solution of propylene glycol methyl ether, with an ethanol mass fraction of 50%; Acrylic hydroxyl emulsion is a polymerized hydroxyl acrylic emulsion with a solid content of 30%.

[0045] Comparative Example 1 A coating, compared with Example 1, is different only in that: no basic hindered amine is added.

[0046] Comparative Example 2 A coating, compared with Example 1, the only difference is that: no 2-(2-hydroxyphenyl)-benzotriazole is added.

[0047] Comparative Example 3 A coating, compared with Example 1, the only difference is that the polysiloxane resin is replaced by water-based polyurethane.

[0048] Comparative Example 4 A coating, compared with Example 1, is different only in that: in the nanoparticles, the mass ratio of nano antimony-doped tin dioxide and nano tungsten-doped tin dioxide is 1:2.

[0049] Comparative Example 5 A coating, compared with Example 1, the only difference is that: in the aqueous dispersion of nanoparticles, the mass fraction of modified nanoparticles is 40%.

[0050] Comparative Example 6 A coating, compared with Example 1, the only difference is that the nanoparticles are not modified by a coupling agent.

[0051] Comparative Example 7 A coating, compared with Example 1, the only difference is that: the weight parts of the nanoparticle aqueous dispersion is 55 parts.

[0052] Comparative Example 8 A coating, compared with Example 1, the only difference is that the weight parts of the polysiloxane resin are 75 parts.

[0053] Comparative Example 9 A coating is prepared according to the formula and method in Example 1 in Patent Publication No. CN115141506A.

[0054] Comparative Example 10 A coating is prepared according to the formula and method in Example 1 in patent publication number CN108504275B.

[0055] Experimental example The coatings in Examples 1-6 and Comparative Examples 1-10 were coated on glass slides to form uniform 20 μm thick coatings. The transmittance of the coatings to ultraviolet light (100-400 nm), infrared light (750-3000 nm), and visible light (GB / T 2680-2021) was tested, as well as the weather resistance of the coatings (exposure to QUV accelerated aging box (240 Hours, 0.68 w / m 2 ), observe the coating discoloration time) and abrasion resistance (tested by pencil hardness method), the test results are shown in the following table:

[0056] Analysis of performance test data shows that the present invention provides a water-based wear-resistant ceramic thermal insulation coating, in which the surfaces of nano-tungsten-doped tin dioxide (GTO) and nano-antimony-doped tin dioxide (ATO) particles are modified with silane, thereby improving the hydrophilicity of the nanoparticles. At the same time, the silane side chains grafted on the surface of the nanoparticles increase the steric hindrance between the particles, significantly improving the dispersibility of the nanoparticles, preventing agglomeration, and dispersing them more evenly in the coating, which can significantly improve the transmittance of the visible light band (the transmittance of visible light in natural light is greater than 82%), and the blocking effect of the infrared band and the ultraviolet band; and through the synergistic effect of 2-(2-hydroxyphenyl)-benzotriazole and alkaline hindered amines with the nanoparticles, the coating can significantly improve its blocking rate for each band of ultraviolet and infrared rays; the total blocking rate for infrared rays in natural light is greater than 90%; and the total blocking rate for ultraviolet rays in natural light is greater than 98%.

[0057] Meanwhile, the present invention adopts organic-inorganic hybrid waterborne silicone resin synthesized by hydrolysis-condensation of silane monomer and silica sol as film-forming material, and its three-dimensional network structure can significantly improve the weather resistance and hardness of the coating.

[0058] The above embodiments describe only the basic principles, main features and / or advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and the invention content of the specification only describe the principles or specific cases of the present invention. Without departing from the essence of the innovative idea of ​​the present invention, the innovative scheme of the present invention may be subject to various changes and improvements, and these changes and improvements all fall within the scope of protection required by the present invention.

Claims

1. A water-based wear-resistant ceramic thermal insulation coating, characterized in that: The invention comprises the following raw material components in parts by weight: 20-50 parts of nanoparticle aqueous dispersion, 50-70 parts of polysiloxane resin, 20-40 parts of acrylic hydroxyl emulsion, 10-20 parts of organic solvent, 0.5-1 parts of 2-(2-hydroxyphenyl)-benzotriazole, and 0.5-1 parts of basic hindered amine; The aqueous dispersion of nanoparticles contains 20-35% by mass of modified nanoparticles, wherein the modified nanoparticles are obtained by modifying the nanoparticles with a silane coupling agent; the nanoparticles are a mixture of nano-antimony-doped tin dioxide and nano-tungsten-doped tin dioxide in a mass ratio of 1-2:5-6; and the alkaline hindered amine is a nitroxide free radical hindered amine.

2. The water-based wear-resistant ceramic thermal insulation coating according to claim 1, characterized in that: The polysiloxane resin is an organic-inorganic hybrid water-based silicone resin formed by hydrolysis and condensation of silane monomers and acidic silica sol.

3. The water-based wear-resistant ceramic thermal insulation coating according to claim 2, characterized in that: The silane monomer is at least one of methyl orthosilicate, ethyl orthosilicate, methyltrimethoxysilane, phenyltrimethoxysilane, dimethyldimethoxysilane and 3-glycidyloxypropyltrimethoxysilane.

4. The water-based wear-resistant ceramic thermal insulation coating according to claim 2, characterized in that: The pH value of the acidic silica sol is 2-4.

5. The water-based wear-resistant ceramic thermal insulation coating according to claim 2, characterized in that: The mass ratio of the silane monomer to the acidic silica sol is 5-10:2-5.

6. The water-based wear-resistant ceramic thermal insulation coating according to claim 1, characterized in that: The acrylic hydroxyl emulsion is a polymerized hydroxyl acrylic emulsion with a solid content of 30%.

7. The water-based wear-resistant ceramic thermal insulation coating according to claim 1, characterized in that: The organic solvent is an ethanol solution of propylene glycol methyl ether or an ethanol solution of ethylene glycol butyl ether.

8. The water-based wear-resistant ceramic thermal insulation coating according to claim 1, characterized in that: The silane coupling agent is a mixture of γ-methacryloxypropyltrimethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane in a mass ratio of 4-10:1-2.

9. The water-based wear-resistant ceramic thermal insulation coating according to any one of claims 1 to 8, characterized in that: The particle size of the nanoparticles is 2-20 nm.

10. The water-based wear-resistant ceramic thermal insulation coating according to any one of claims 1 to 8, characterized in that: The preparation method of the nanoparticle aqueous dispersion comprises: adding the modified nanoparticles into deionized water, then adding an aqueous dispersant and an aqueous wetting agent, and dispersing the aqueous dispersion by ultrasonic for 2-3 hours to obtain the nanoparticles.

Citation Information

Patent Citations

  • A UV-blocking, high-transmittance, temperature-controlled glass coating and its preparation method

    CN108504275B

  • Environment-friendly transparent heat insulation coating and preparation method thereof

    CN115141506A

  • Transparent thermal insulation anti-ultraviolet coating and preparation method thereof

    CN101899249A

  • Tungsten doped tin dioxide nano powder and preparation method thereof

    CN103449508A

  • Tungsten-doped stannic oxide sol nanocrystalline and preparing method thereof

    CN105540650A